Travels through Norway and Lapland during the years 1806, 1807, and 1808 - Buch, Leopold von 1774-1853 (Cambridge University Press, 2011)
In Travels Through Norway and Lapland, Leopold von Buch (1774-1853), a German geologist and palaeontologist, recounts his expedition to Scandinavia in 1806-1808. This book, originally published in Berlin in 1810, and in this English translation in 1813, describes these large, sparsely populated regions at the turn of the nineteenth century. The translator's preface provides an important geo-political backdrop - the possibility of war in Norway and the machinations of Sweden, Russia and Great Britain over the future of this territory. Von Buch's observations, however, are firmly engaged with the scientific. He writes that his motivation for the expedition was to find out how the harsh climate influenced the land, and he records detailed information about the weather and the region's mineralogy and geological structure. He also describes the local population, providing a wide-ranging account of life in the remote reaches of Northern Europe.
Keywords: Lapland -- Description and travel.; Norway -- Description and travel.